(3GdJMaI GdMSjfjIs - (3GdHgHgGfj, eMeO GdHgHgGfj, eMeO HGbQ Hf eMeO Cced GdCUagGfj, J (B1205(3g` (B1891(3es ((3GdeTgO GdMSjfjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3CYde Cf GdWgGQI Ydi bSejf, bSe jJhba Ydi GdfjI hjSei HGdWgGQI Yf GdMOK hfMh Pdc, hbSe dG jJhba Ydi GdfjI hjSei HGdWgGQI Yf GdNHKs
(3BNQgG (B:s
(3BNQgG(B: (3hEf cGfJ eeG dG JMUi heG Hjf GdeVGHjf Yah CjkVG hcPG Hjf cd fUGHjf ef GdfUGH hGdKGfj EP GdfUGH GdKGfj ajg CjkVG djS hGMO Hd cd CQHYjf OQgeG fUGH hEf HdZ EdGa Cda dG jMUis
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf L (B3: 154s
(3GdPQjYI, L (B3: 233s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis